THE ROLE OF SOCIO-ECONOMIC FACTORS IN THE FORMATION OF POPULATION HEALTH IN THE CONTEXT OF THE REGIONS OF KYRGYZSTAN (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The relationship between socio-economic indicators and life expectancy (LE) of the population in the context of the regions of Kyrgyzstan was studied. Correlation analysis revealed a negative relationship between life expectancy and the number of labor force and employed population in 5 subjects of Kyrgyzstan - in Batken, Jalal-Abad, Issyk-Kul, Naryn and Chui regions, with the exception of Osh region, where a positive relationship was established. A positive relationship has been established between life expectancy and indicators of monetary income and expenditure of the population, as well as the average monthly wage in all regions. A negative relationship was shown between life expectancy and the level of general unemployment in all regions, with the exception of Jalal-Abad and Issyk-Kul regions. A study of the relationship between life expectancy and the level of poverty showed a negative relationship in all regions, with the exception of Chui oblast, where a positive relationship was noted. It has been established that the socio-economic condition is an important determinant of life expectancy for the regions of Kyrgyzstan in the period from 2005 to 2020.
Keywords: life expectancy; socio-economic parameters; regions of Kyrgyzstan